Comment on: Behçet disease in Emergency Department: a rare case presenting with haemoptysis and massive pulmonary arterial aneurysms. On behalf of the Hughes-Stovin syndrome (HSS) international study group - Emad, Yasser; Ragab , Yasser; Rasker, Johannes (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Pulmonary vasculitis in Hughes Stovine syndrome and Behçet disease are often similar relative to clinical presentations and the typical computed tomography pulmonary angiographic findings. Unstable pulmonary artery pseudo-aneurysm (PAP), is considered by far the most serious CTPA sign with unpredictable course Furthermore the close intimate relationship between the false aneurysmal wall in PAP and the adjacent bronchus is a very critical and serious CTPA sign that should be early identified and urgently managed.